2017
DOI: 10.3390/molecules22071191
|View full text |Cite
|
Sign up to set email alerts
|

Cardamom, Cumin, and Dill Weed Essential Oils: Chemical Compositions, Antimicrobial Activities, and Mechanisms of Action against Campylobacter spp.

Abstract: Natural antimicrobials as well as essential oils (EOs) have gained interest to inhibit pathogenic microorganisms and to control food borne diseases. Campylobacter spp. are one of the most common causative agents of gastroenteritis. In this study, cardamom, cumin, and dill weed EOs were evaluated for their antibacterial activities against Campylobacter jejuni and Campylobacter coli by using agar-well diffusion and broth microdilution methods, along with the mechanisms of antimicrobial action. Chemical compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(28 citation statements)
references
References 62 publications
(79 reference statements)
1
24
1
Order By: Relevance
“…Mutlu-Ingok et al studied the antibacterial activities of cardamom, cumin, and dill weed EOs against Campylobacter jejuni and Campylobacter coli . The results indicated that EOs might be effective inhibitors by directly acting at the bacterial membrane integrity level [49]. It is important to highlight that EOs derived from oregano, thyme, clove, and arborvitae also showed a very strong antibacterial activity against other bacteria causing foodborne disease; therefore, they can be used as antimicrobial agents [57].…”
Section: Discussionmentioning
confidence: 99%
“…Mutlu-Ingok et al studied the antibacterial activities of cardamom, cumin, and dill weed EOs against Campylobacter jejuni and Campylobacter coli . The results indicated that EOs might be effective inhibitors by directly acting at the bacterial membrane integrity level [49]. It is important to highlight that EOs derived from oregano, thyme, clove, and arborvitae also showed a very strong antibacterial activity against other bacteria causing foodborne disease; therefore, they can be used as antimicrobial agents [57].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Teneva and coworkers [ 33 ] reported that the green cardamom oil (chemotype α-terpinyl acetate 39.03 %, eucalyptol 31.53 %) was active against pathogenic E. coli ATCC 25922, E. coli ATCC 8739, Salmonella sp., S. aureus ATCC 6538P, and P. vulgaris strains with a diameters of inhibition zones between 8 and 10 mm and MICs values from 60 to >600 ppm. In 2017, Mutlu-Ingok and Karbancioglu-Guler [ 34 ] reported that the green cardamom oil (chemotype α-terpinyl acetate 43.4%, eucalyptol 29.2%) was active against Campylobacter jejuni and Campylobacter coli with a diameter of growth inhibition zone ranging from 24.75 mm to 25.58, respectively. The MICs and MBCs values were low for the two Campylobacter strains tested (0.025 µL/mL).…”
Section: Discussionmentioning
confidence: 99%
“…This was particularly noticeable on the S. aureus bacteria suggesting the release of electrolytes from within the cells by cellular leakage. Indeed, the lysis and death of the bacteria by the action of ampicillin or the EOs may have lead the bacteria to release the intracellular content and with electrolytes such as K + , Ca 2+ , and Na + capable of raising the conductivity of the solution [51]. Considering the EOs primary mechanism of action against bacteria resorts to the accumulation of biomolecules at their surface, disturbing its structure and functionality, it is likely the content leakage to be the result of their interaction with the cytoplasmic membrane [25].…”
Section: Cell Membrane Permeabilitymentioning
confidence: 99%